2011
DOI: 10.1007/s00262-011-1028-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated myeloid-derived suppressor cells in pancreatic, esophageal and gastric cancer are an independent prognostic factor and are associated with significant elevation of the Th2 cytokine interleukin-13

Abstract: We undertook a comprehensive analysis of circulating myeloid-derived suppressor cells (MDSCs) and T regulatory cells (Tregs) in pancreatic, esophageal and gastric cancer patients and investigated whether MDSCs are an independent prognostic factor for survival. We evaluated a series of plasma cytokines and in particular re-evaluated the Th2 cytokine interleukin-13 (IL-13). Peripheral blood was collected from 131 cancer patients (46 pancreatic, 60 esophageal and 25 gastric) and 54 healthy controls. PBMC were har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
414
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(452 citation statements)
references
References 25 publications
22
414
3
3
Order By: Relevance
“…We found that plaGR-MDSCs led to a polarization of CD4 + T cells toward a Th2 phenotype. This is in line with studies in mice and humans showing an association between MDSC count and Th2 cytokine expression (15,(57)(58)(59). The present study, however, is to our knowledge the first to show a direct impact of MDSCs on T cell polarization in humans.…”
Section: Discussionsupporting
confidence: 67%
“…We found that plaGR-MDSCs led to a polarization of CD4 + T cells toward a Th2 phenotype. This is in line with studies in mice and humans showing an association between MDSC count and Th2 cytokine expression (15,(57)(58)(59). The present study, however, is to our knowledge the first to show a direct impact of MDSCs on T cell polarization in humans.…”
Section: Discussionsupporting
confidence: 67%
“…The importance of CD4 + IL-4 + cells in malignancy was recently demonstrated in a mouse mammary carcinoma model, in which production of IL-4 by helper T cells was able to polarize macrophages, resulting in increased lung metastasis [6]. Similarly, increased plasma levels of IL-13 in patients with pancreatic, gastric and esophageal cancers was positively correlated to increased numbers of myeloid derived suppressor cells [51]. Both these studies showed important downstream effects of the shift to a type 2 response, but did not examine the preliminary cause of the shift.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, IL-1β has been found to up-regulate TNF-α concentrations in the tumor microenvironment through induction of the production of latter cytokine by myeloid and/or tumor cells [71,72]. In addition, IL-1β has been shown to stimulate the production of IL-10, IL-5 and IL-13, which induced type 2 immune reactions and attracted MDSCs to the tumor site [73,74]. Finally, it has been recently reported that IL-1β could induce and maintain tumor angiogenesis by stimulating the VEGF production [66,75].…”
Section: General Characteristic Of Mdscsmentioning
confidence: 99%